PENINGKATAN PENDAPATAN KERUPUK CITRA MELALUI PENINGKATAN KUANTITAS DAN KUALITAS PRODUKSI - Yuliastuti, Ida Ayu Nyoman; Lestari, I Gusti Agung Ayu Istri; Purnawati, Ni Luh Gede Putu (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2018)
Cracker or Kerupuk is one of the most popular snack in Indonesia and it can be a business opportunity through a million rupiahs of sales. This opportunity is utilized by Mr. I Putu Soma Antara (40 years old) by setting up a home-made cracker?s business line "Citra". Mr. Putu Soma Antara who called his crackers as ?Kerupuk Rante? usually produce approximately 10 kilograms of raw materials. Thirty large packs of crackers are ready to sell per day and wrapped it in a fourteen small package. Mr. Putu Soma Antara made the crackers next to his house. The condition of the production place is not feasible to make crackers. The kitchen appliances are damaged. The kitchen table is obsolete. He does not have some kitchen appliances such as frying pan, steamer, and pressing machine. In accordance with the problems faced by business partner, this study provides some solutions. First, the improvement of production site. Adding some kitchen appliances for example kitchen table, pressing machine. This study also gives training for packaging product, selling and marketing skill and simple bookkeeping assistance to Mr. Putu Soma. From the solution that has been given, the production capacity of crackers Citra increasing from 10 kilograms to 20 kilograms in a day and the production site becomes more comfortable because the equipment has been improved and the quality of product becomes more hygienic. With the increasing quantity and quality of production then orders received by Mr. Putu Soma also increased, this imply that income received by the business Crackers Citra also increased.